TGFβ signaling pathways in human health and disease - Chen, Pei-Yu; Qin, Lingfeng; Simons, Michael (Frontiers in molecular biosciences, 2023)
Transforming growth factor beta (TGFβ) is named for the function it was originally discovered to perform-transformation of normal cells into aggressively growing malignant cells. It became apparent after more than 30 years of research, however, that TGFβ is a multifaceted molecule with a myriad of different activities. TGFβs are widely expressed with almost every cell in the human body producing one or another TGFβ family member and expressing its receptors. Importantly, specific effects of this growth factor family differ in different cell types and under different physiologic and pathologic conditions. One of the more important and critical TGFβ activities is the regulation of cell fate, especially in the vasculature, that will be the focus of this review.